Decision dashboards to make evidence more accessible for decision makers through the Landscape Portal - CGIAR Research Program on Water, Land and Ecosystems (2021)
Dashboards have been developed for Ethiopia, Kenya, Malawi, Tanzania and Zambia, offering decision makers a practical resource they can use to obtain a quick overview of a situation and respond with appropriate and effective strategies. The dashboards can be accessed through the Landscape Portal.